PEMETAAN PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN AKUNTANSI KELAS XI IPS DI SMA NEGERI 13 SURABAYA TAHUN AJARAN 2012/2013 - GAUTAMA PUTRA, ADITYA (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Research on the use of evaluation tools evaluation tools from accounting subjects aimed to determine the extent of the feasibility from the evaluation tool accounting subjects in grade XI Social in SMA Negeri 13 Surabaya. This type of research is descriptive research. Data collection techniques in this study using the documentation which has been obtained from the school, and direct interview techniques to the accounting teacher in grade XI Social in SMA Negeri 13 Surabaya. Whereas the data analysis techniques used are documentation techniques to answer the evaluation tools used. And then, using interview techniques to answer the reason from the the use of the evaluation tools. The feasibility of evaluation tools was examined using a qualitative analysis based on expert review of sheet. The results showed the results that the evaluation tools used is multiple choice test and essay test. The final semester exam is a multiple choice test with 4 packs exam questions. Teachers choose this multiple-choice test because it contains many questions about the theory rather than the question counting. The review sheet from the experts said the percentage of The final semester exam of packet 1 is 73,79% with a feasible category. Same as the percentage packet 1, the percentage of packet 2 is 80,42% with a feasible category. whereas the percentage of packet 3 is 86,08% with a very feasible category. The last, the percentage of packet 4 is 89,04% with a very feasible category. The conclusion from the this research stated that the multiple choice of evaluation tools used in SMA 13 Surabaya feasible for use by teachers and students in the evaluation program of learning outcomes. Keywords: Evaluation tools, Feasibility, Accounting